Are General Insurance Companies Efficient in their Performance? – A Comparison - Muthulakshmi, P (Ushus Journal of Business Management, 2018)
The insurance sector has witnessed significant changes in the last few years, specifically due to the effects of liberalisation, globalisation, and privatisation. It is imperative to compare and study the earnings and profitability of public sector non-life general insurance companies in India. The public sector non-life general insurance companies are competing with each other, and also with the private players in the same industry and thereby reducing the processing costs and facilitating the innovation of different types of policies across the geographic boundaries. In this paper, secondary data is used to analyse the earnings and profitability of non-life general insurance companies in India by using certain ratios which are available exclusively to evaluate the performance of insurance companies such as Claim Ratio, Expenses Ratio, Combined Ratio, Investment Income Ratio and Return on Equity Ratio. , , , Ratio Analysis